English morphosyntactic performance of a high functioning ASD child: Implications on ELT - Mohd Yusoff, Yusniza; Salehuddin, Khazriyati; Abdullah, Imran Ho; Toran, Hasnah (Universiti Utara Malaysia Press, 2019)
Purpose – The inclusion of an increasing number of highfunctioning ASD children in mainstream classrooms demands for adequate awareness of autism and effective teaching methods from teachers to ensure that learning takes places efficiently. Hence, this study investigated the atypical language performance of a highfunctioning Malay girl with autism spectrum disorder (ASD), who chose to acquire English as her first language (L1) and eventually spoke the language fluently despite English not being the main language at home. Focus was given on the child’s literate language use of morphology and syntax in present tense English. Methodology – Data was collected from spontaneous speech interactions with an 8-year-old high-functioning ASD child for a period of 12 months. The interactions were conducted at the child’s home. Each session lasted approximately an hour and was video recorded. The data was analyzed using thematic analysis. In this study, focus was given on the morphology and syntax of the child’s present tense structures in English.Findings – The findings revealed four main themes: 1) elaborated noun phrases, 2) adverbs, 3) conjunctions, plus 4) mental and linguistic verbs. The findings indicated the child’s strength in her language performance that was consistent albeit with weak central coherence account and that she was not at the optional infinitive stage of grammatical development.Significance – These findings led to a further understanding of the language acquisition process in high-functioning children with ASD in Malaysia, and called for mainstream teachers to 1) upgrade their skills, enhance their knowledge and develop their awareness of the linguistic ability of high-functioning ASD children, and 2) implement effective teaching methods in managing them.